Pendekatan Antropologis dalam Pengkajian Islam: Memahami Islam Sebagai Praktik Sosial-Budaya - Kurniawati, Yayah; Syukur, Umi Jamilatus; Budiyanto, Agus; Zaenal (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Islamic studies often predominantly utilize a normative-theological approach, thus the empirical dimensions and practices of religiosity in socio-cultural life have not always received adequate attention. This article aims to analyze the anthropological approach in Islamic studies and its relevance to understanding Islam as a socio-cultural practice. This research uses a qualitative method with a library research approach. Data sources were selected purposively based on their relevance to the theme of the anthropological approach in Islamic studies, including national and international journal articles, books, and previous research results. Data were analyzed through the stages of identification, classification, interpretation, and descriptive-analytical analysis of relevant ideas and findings. The results of the study indicate that the anthropological approach views Islam as a living phenomenon manifested through rituals, symbols, religious institutions, and patterns of social interaction among Muslims in various local contexts. This approach complements the normative-theological approach by presenting an empirical-contextual perspective, so that the relationship between normative Islam (great tradition) and Islam as practiced in everyday life (little tradition) can be understood more fully. This study recommends strengthening the anthropological approach as part of the methodology of multidisciplinary Islamic studies in religious universities.